2016
DOI: 10.1155/2016/6720947
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Gene Expression in an Inbred Line of Soft-Shell Clams (Mya arenaria) Displaying Growth Heterosis: Regulation of Structural Genes and the NOD2 Pathway

Abstract: Mya arenaria is a bivalve mollusk of commercial and economic importance, currently impacted by ocean warming, acidification, and invasive species. In order to inform studies on the growth of M. arenaria, we selected and inbred a population of soft-shell clams for a fast-growth phenotype. This population displayed significantly faster growth (p < 0.0001), as measured by 35.4% greater shell size. To assess the biological basis of this growth heterosis, we characterized the complete transcriptomes of six individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…In the present analysis, no enough evidence was promulgated to authenticate the existing association between NOD2 and kidney cancers. More sequencing data and studies on the mechanism of cancer occurrence and clinical trials about NOD2 gene, such as inflammation and immune disease area [ 25 , 26 ], are needed to further reveal the specific mechanism of action in kidney cancer areas.…”
Section: Discussionmentioning
confidence: 99%
“…In the present analysis, no enough evidence was promulgated to authenticate the existing association between NOD2 and kidney cancers. More sequencing data and studies on the mechanism of cancer occurrence and clinical trials about NOD2 gene, such as inflammation and immune disease area [ 25 , 26 ], are needed to further reveal the specific mechanism of action in kidney cancer areas.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the GO term findings supported the higher growth rates and activity levels of F individuals in comparison with S mussels. Not surprisingly, previous works on interindividual growth rate differences in bivalves have also described similar GO terms as the main processes underlying growth differences; for instance, Wilson et al (2016) reported that 19% of GO terms of differentially expressed genes in fast-growing Mya arenaria are associated with cell structure, whereas 17% refer to signalling and growth, 12% to energy and nutrient metabolism and 10% to DNA/RNA and protein synthesis. Regarding the KEGG terms, energetic metabolism terms were referred to F individuals in good correspondence to their higher activity levels.…”
Section: Accepted Manuscriptmentioning
confidence: 93%
“…More recently, De la Peña et al (2016) reported the existence of significant differences in the rate of expression of ferritins (Apfer1) between fast-and slow-growing individuals of Argopecten purpuratus at different developmental stages (5 stages from embryos to juveniles). Wilson et al (2016) produced an inbred fast growth line (F) of Mya arenaria clams and analysed the gene expression to test the hypothesis that specific growthrelated genes will be upregulated in F individuals. These authors established a positive correlation between some metabolic genes (fatty acid synthase and ATPase) with fast growth.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation